PERKEMBANGAN SOSIO-EMOSIONAL ANAK DENGAN ORANGTUA YANG MENGALAMI PERCERAIAN DI ASRAMA PUTERI WALTERUS - Jansi Pangkey; Mozes M. Wullur; Gloridei L. Kapahang (PSIKOPEDIA, 2022)
The purpose of this research is to identify and analyze the socio-emotional development of children of divorced parents. The method used in this research is qualitative and the type of research is a case study. The subjects of this research are the eighth grader of junior high school whose parents divorced. Data collection methods used are interviews and observation. Research data validation uses source triangulation in which the researcher interviews the closest people to the subject. The results of this research evidences that children’s social-emotional development tends to be influenced by parental divorce. It is reflected in the expression of emotions, relationships with other people, behavior, and also the results of the study.